Biorefinery integration of microalgae production into cassava processing industry: Potential and perspectives. (January 2018) - de Carvalho, Júlio Cesar; Borghetti, Ivo Alberto; Cartas, Liliana Carrilo; Woiciechowski, Adenise Lorenci; Soccol, Vanete Thomaz; Soccol, Carlos Ricardo
Highlights: Cassava processing waste (CPW) is generated annually in a volume of 170 billion liters. 11% of the crop energy is lost in CPW. Biogas production from CPW can be integrated into microalgae culture. Wild isolates grow in raw and pretreated residue, effectively treating it. Abstract: Cassava, the 5th most important staple crop, generates at least 600L of wastewater per ton of processed root. This residue, cassava processing wastewater (CPW) has a high chemical oxygen demand, that can reach 56 g/L, and has also high concentrations of several mineral nutrients. The cultivation of microalgae such as Chlorella, Spirulina and wild strains was evaluated in the last years in raw, minimally processed and partially digested CPW. Concentrations of 2–4 g/L of these microalgae, comparable to those obtained in synthetic media, could be reached. The BOD of the residue was reduced by up to 92%. This process can be integrated into cassava processing industries, if challenges such as the toxicity of the concentrated residue, bacterial contamination, and the isolation of robust strains are addressed. Because CPW carries about 11% of the crop energy, integrating biogas production and microalgal cultivation into the cassava processing chain is promising.